Munich - Ledig, Elfriede 1955-; Gale Group (London Dorling Kindersley Limited, 2015)
Provides background information on Munich; recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.
Munich's top 10 -- Around town -- Day trips & excursions -- Streetsmart.
Includes bibliographical references and index.
Keywords: Munich (Germany) -- Guidebooks